IL-22 suppresses HSV-2 replication in human cervical epithelial cells. (November 2019) - Xu, Xi-Qiu; Liu, Yu; Zhang, Biao; Liu, Hang; Shao, Dan-Dan; Liu, Jin-Biao; Wang, Xu; Zhou, Li-Na; Hu, Wen-Hui; Ho, Wen-Zhe
Highlights: Human cervical epithelial cells (HCEs) express the functional IL-22 receptor. IL-22 inhibits HSV-2 replication in HCEs. IL-22 induces the expression of ISGs and the tight junction proteins in HCEs. IL-22 has potential as a therapeutic agent to inhibit HSV-2 infection. Abstract: Interleukin (IL)-22, a member of the IL-10 family, plays a role in antiviral immune responses to a number of viral infections. However, it is unclear whether IL-22 is involved in the mucosal immunity against herpes simplex virus 2 (HSV-2) infection in the female reproductive tract (FRT). In this study, we studied whether IL-22 could inhibit HSV-2 infection of human cervical epithelial cells (End1/E6E7 cells). We showed that End1/E6E7 cells express the functional IL-22 receptor complex (IL-22R1 and IL-10R2). When treated with IL-22, End1/E6E7 cells expressed the higher levels of IFN-stimulated genes (ISGs: ISG15, ISG56, OAS-1, OAS-2, and Mx2) than untreated cells. In addition, IL-22-treated cells produced higher levels of the tight junction proteins (ZO-1 and Occludin) than untreated cells. Mechanistically, IL-22 could activate the JAK/STAT signaling pathway by inducing the phosphorylation of STAT1 and STAT3. These observations indicate the potential of IL-22 as an anti-HSV-2 agent in the FRT mucosal innate immunity against HSV-2 infection.